HUBUNGAN TIPE MALFORMASI ANOREKTAL, KELAINAN KONGENITAL PENYERTA, SEPSIS, DAN PREMATURITAS DENGAN MORTALITAS PASIEN MALFORMASI ANOREKTAL - Bima Indra; Shalita Dastamuar; Rahmadr Hidayat (Majalah Kedokteran Sriwijaya, 2018)
Anorectal malformations are a broad spectrum of anal and rectal disorders ranging from stenosis to anorectal agenesis. The incidence of mortality in cases of anorectal malformations is influenced by many factors, including the type of anorectal malformation, associated congenital anomalies, sepsis, and prematurity as investigated in this study. This study aims to identify the association between anorectal malformation type, associated congenital anomalies, sepsis, and prematurity with mortality on anorectal malformation patient. This research is an observational analytic study with cross sectional study design. Secondary data collection was obtained from eighty-two medical records of anorectal malformation patients in Dr. Mohammad Hoesin Hospital Palembang from January 2015 to June 2017 that meets the inclusion criteria. Of the eighty-two cases of anorectal malformations, nineteen cases of mortality (23.2%) were obtained. Of the four risk factors studied, two risk factors were found to significantly affect the mortality of anorectal malformation patients, they are anorectal malformation type (p value = 0.036) and sepsis (p value = 0.049). Factors that have significant correlation to mortality of patients with anorectal malformations are the type of anorectal malformations and sepsis, whereas associated congenital anomalies and prematurity have no effect on the mortality of patients with anorectal malformations.